The impact of omentectomy on cause-specific survival of Stage I–IIIA epithelial ovarian cancer: A PSM–IPTW analysis based on the SEER database - Hao, Zhimin; Yu, Yangli; Yang, Sufen (Frontiers in Surgery, 2022)
Abstract Objective: Routine omentectomy is generally performed at time of surgery for patients with epithelial ovarian cancer (EOC). The current study was aimed to evaluate the impact of omentectomy on cause-specific survival of stage I-IIIA EOC patients. Methods: Patients who presented with clinical stage I-IIIA serous, clear cell, endometrioid and mucinous ovarian cancer were selected from the SEER Database between 2004 and 2018. We extracted clinocopathological data and surgery information with the focus of performance of omentectomy and lymphadenectomy. Binary logistic regression and recursive partitioning analyses were conducted to identify the significant factors for performance of omentectomy at surgery. Propensity score matching (PSM) and inverse probability treatment weighting (IPTW) technique were utilized to balance confounding factors. Multivariate, exploratory subgroup analyses and sensitivity analyses were respectively conducted to evaluate impact of omentectomy on cause-specific survival (CSS). Results: A total of 13302 patients with EOC were enrolled in the analysis. The cohort comprised 3569 endometrioid, 4915 serous, 2407 clear cell, 2411 mucinous subtypes. 48.62% (6467/13302) of patients underwent the omentectomy during primary surgery, only 3% absolute improvement of CSS at individual period was observed, without statistical significance based on multivariate analysis. According to regression-tree model with recursive partitioning analysis, the procedure of lymphadenectomy was found to be the strongest factor to distinguish performance of omentectomy, followed by tumor stage. Patients who underwent omentectomy were more likely to be managed in stage I patients and those with lymphadenectomy performed. After PSM-IPTW adjustment, inclusion of omentectomy at initial surgery did not demonstrate beneficial impact on CSS compared to those not. Exploratory subgroup analysis indicated performance of omentectomy improved 5-year CSS in stage II-IIIA paitents. In the sensitive analyses for various tumor stages, omentectomy appeared to only benefit stage II patients. However, patients across various stages seemed to benefit from performance of lymphadenectomy, irrsespective of omentectomy performed. Conclusion: Routine omentectomy may not be associated with a survival benefit for patients with grossly normal-appearing omentum, especially clinical stage I epithelial ovarian cancers.